The Problem of "Construction" and "Self-Construction" of The Identity of a Mestizo-Migrant Subject: The Case of Ernesto, In The Deep Rivers, of Arguedas - Solé Zapatero, Francisco Xavier (2022)
As is well known, the problem of the identity of heterogeneous, transculturated and bi-pluri-sociocultural Latin American beings, whatever the position and perspective from which it is faced and whatever the way in which it is investigated, today is, as a whole, a problem of an abysmal magnitude. And although it is true that this problem is born with the real encounter between two worlds: the European and the indigenous (although, properly speaking, it was already present before, given the encounters between the various ethnic groups), and that from the very beginning it becomes the subject of deep debate and extensive polemics, it will not be until the twentieth century that it becomes a deeply encompassing and almost properly incomprehensible topic, from any angle that visualizes it. This was the main reason that led us to try to center, delimit and concretize as much as possible our proposal of dialogical-chronotopic hetetrogeneous-transculturated analysis of this complex and all-encompassing problem for the case of Ernesto, narrator and character of Deep rivers, by José María Arguedas, for which we will use the reading proposals offered by the "Process of successive-cumulative approaches" (PSCA).